1984
DOI: 10.1159/000466179
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Monoclonal Antibodies with Anti-A, Anti-B and Anti-A,B Specificities; Some Superior to Human Polyclonal ABO Reagents

Abstract: A series of fusions using mouse myeloma cells and spleen cells from mice immunized with blood group substances or human red cells was performed with the aim of obtaining ABO antibodies suitable for routine blood grouping. Seven strongly agglutinating antibodies against antigens in the ABO system were obtained from 18 fusions. These antibodies were tested extensively in manual and automated routines, and six of them were found to be as good as or better than commercial polyclonal test sera of human origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…1) the specificity of which was confirmed by absorption with blood group A RBC (data not shown). The difference between the A and B determinants may be related to the presence of B-like struc tures on mouse RBC as previously noted [17,18]. In accord ance with this result, Balb/c mouse RBC were agglutinated much more strongly by human hyperimmune anti-B (2+) than anti-A (w) reagents.…”
Section: Natural Abo Immunity In Balb/c Micesupporting
confidence: 75%
“…1) the specificity of which was confirmed by absorption with blood group A RBC (data not shown). The difference between the A and B determinants may be related to the presence of B-like struc tures on mouse RBC as previously noted [17,18]. In accord ance with this result, Balb/c mouse RBC were agglutinated much more strongly by human hyperimmune anti-B (2+) than anti-A (w) reagents.…”
Section: Natural Abo Immunity In Balb/c Micesupporting
confidence: 75%
“…The main conclusion of this study, in agreement with Messeter et al [45], is that some monoclonal antibodies are better agglutinating reagents for some weak A or B variants than the conventional polyclonal antibodies.…”
Section: Binding Of P1a2 and P1a4 On Glycolipids Separated By Thin-lasupporting
confidence: 92%
“…Investigation revealed that the blood donors concerned had elevated levels of the B-determining enzyme, D-galactosyltransferase, and that this enzyme in addition to its nor mal function of transferring Z)-galactose to the acceptor substrate has the capacity to transfer the A-determining sugar N-acetyl-Z)-galactosamine. Incidentally, Beck et al [15] pointed out that the in vitro biosynthesis of blood group B determinants by the A transferase had been demon strated by Yates and Watkins [16], and predicted that a similar phenomenon would be observed using potent monoclonal anti-B reagents with group A cells. This has in fact been noted by Sonneborn and Voak [17] and more recently by ourselves.…”
Section: Discussionmentioning
confidence: 99%